Iraq's Tourism Potential - Dabidian, Hooman (World Bank, Washington, DC, 2016)
While it will require further political stability and security, tourism in Iraq stands to be a major growth sector. The Iraqi tourism sector is currently underdeveloped and in a state of neglect, due to decades of war, closed regimes and recurrent instability and insecurity. However, as Iraq continues to develop and stabilizes, it can begin to meet its tremendous potential as a global tourist destination, and gain the associated economic benefits. A more developed tourism sector in Iraq will play an important role in diversifying Iraq's economy and providing new private sector jobs, both in major cities and beyond. Iraq's construction sector will also benefit directly from the building of hotels, museums, restaurants, and other attractions as well as needed infrastructure enhancements. In addition to construction activity, the private sector can manage, operate and maintain sector-specific infrastructure, as well as provide job opportunities as tour guides, operators and in travel agencies and beyond. With increased interest in Iraq's historic and archaeological sites, Iraq can further improve its archeological capacity with skills needed in excavation, restoration, and reconstruction work.